If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -2)(4x + 8) = 0 Reorder the terms: (-2 + 2x)(4x + 8) = 0 Reorder the terms: (-2 + 2x)(8 + 4x) = 0 Multiply (-2 + 2x) * (8 + 4x) (-2(8 + 4x) + 2x * (8 + 4x)) = 0 ((8 * -2 + 4x * -2) + 2x * (8 + 4x)) = 0 ((-16 + -8x) + 2x * (8 + 4x)) = 0 (-16 + -8x + (8 * 2x + 4x * 2x)) = 0 (-16 + -8x + (16x + 8x2)) = 0 Combine like terms: -8x + 16x = 8x (-16 + 8x + 8x2) = 0 Solving -16 + 8x + 8x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '8'. 8(-2 + x + x2) = 0 Factor a trinomial. 8((-2 + -1x)(1 + -1x)) = 0 Ignore the factor 8.Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-2, 1}
| 375=15s+75 | | 5x+6-3x-3=6 | | 7(2a-4b)-3(4a-2b)= | | P+30.34= | | 3x^2-6x+4=13 | | 6x+3(2x+8)=120 | | 8x=2+y | | (22b-1)-7(3b+3)=-6 | | 5x(2x^2-3x+3)= | | C=15s+75 | | =90-70 | | 2y^2-y-36=0 | | 2x+25=3 | | 8x(9x+5)= | | 6s-17=-8+3s | | x*87=87 | | 3k+15-9=2(1k+2) | | 6r-15=0+r | | 5x-3(x-1)=7 | | 7-3x+5when=2 | | x(x+40)=180 | | 6p+5[3(2-3p)-2(5-4p)]= | | -42=7(8-x) | | (3x-5)+(6x-40)=90 | | (3x-5)+(6x-40)= | | -7x+10=10-7x | | 4a^2-17a-15=0 | | -5y^2+8y+7=0 | | 45/6b+4111/140=4/5b-22/5+11/7 | | 8x(9x)= | | x=(x+40) | | =2+2sin(i) |